PEMBATAS KHALWAT DIRUNUT DARI AYAT-AYAT AL-QURAN: KAJIAN TAFSIR MAUḌŪ`IY BERDASARKAN URUTAN TURUNNYA SURAT - Yayan Musthofa; Roem Rowi (Tahkim (Jurnal Peradaban dan Hukum Islam), 2021)
Khalwat between couples, both those who are related by blood or who are not; physically long-distant relationships or close ones like the servant’s routine often ignored by moslems. This relationship is considered to have continued for forefathers, without any awareness and knowing deeply obout this relationships in view of Islam, although this religion (Al-Quran) already give the borders between its to keep privacy and honor to each person who believe. The studies use library research with maudū’iy interpretation approach, which is classifying Al-Quran verses related to the discussion of khalwat in fiqh and tafsir books. Then falsified sort, and selected which are more touching on the topic of discussion. From several verses that have been selected then analyzed to produce conclusion. This study concludes there are three barriers (hijab, septum, or veils) that separate the couples non-marriage. These mandatory barriers are hijab, sense, and times. Keywords: khalwat, hijab (veils), , mauḍū’iy, interpretations.